Small Arms and Light Weapons (SALWs) Proliferation: A Threat to Peace and Security in Mangu Local Government Area, Plateau State, Nigeria - Shipurut, Geoffrey Nanbal; Adi, Amos Joyce; Adenugba, Omolola Abiodun (Darul Yasin Al Sys, 2025)
The proliferation of Small Arms and Light Weapons (SALWs) in Mangu Local Government Area (LGA) has exacerbated violent conflict, undermined social cohesion, and posed significant challenges to peace and security due to weak governance, socio-economic vulnerabilities, and ineffective conflict resolution mechanisms. This study aims to investigate the impact of Small Arms and Light Weapons (SALWs) proliferation on peace and security in Mangu Local Government Area, Plateau State, Nigeria. The study used a descriptive, cross-sectional survey research design. A sample size of 400 respondents was selected from the total population of 442,100 using the Tare Yamane formula. Questionnaires were distributed to 400 randomly selected participants across all the wards in Mangu LGA. Interviews were also conducted with six key informants to complement the data gathered from the questionnaires Responses from the questionnaires were analysed using descriptive statistics of frequency counts and percentages. Qualitative data were analysed while outlining the key point presented by the key informant. The study revealed that the proliferation of Small Arms and Light Weapons (SALWs) is a major threat to peace in Mangu LGA, fueling violence, insecurity, and social fragmentation. Key drivers include socio-economic challenges and ineffective governance, necessitating urgent, comprehensive interventions to restore stability and trust. The study recommends strengthening border security, promoting community dialogue, addressing socio-economic challenges, improving governance, and launching disarmament programs to mitigate the impact of SALW proliferation in Mangu LGA.